Neutrophil-to-lymphocyte ratio, nucleated red blood cells and erythrocyte abnormalities in canine systemic inflammatory response syndrome. (October 2019) - Pierini, A.; Gori, E.; Lippi, I.; Ceccherini, G.; Lubas, G.; Marchetti, V.
Abstract: Systemic inflammatory response syndrome (SIRS) is the manifestation of the systemic response to an infectious or non-infectious disease. We evaluated the association between erythrocyte parameters, including nucleated red blood cells (NRBCs) and leukocyte ratios (NLR, neutrophil-to-lymphocyte ratio; BLR, band neutrophil-to-lymphocyte ratio; BLNR, band neutrophil-to-neutrophil-to-lymphocyte ratio). A review of the medical records was conducted searching SIRS dogs among those admitted to our intensive care unit and a SIRS grading was obtained based on how many criteria were fulfilled. The Acute Patient Physiology and Laboratory Evaluation (APPLEfast ) score was assessed in each dog. Survival rate was assessed 15 days after admission. Dogs with clinical and/or clinicopathological signs of hemolytic or hemorrhagic disorders were excluded. Dogs with ≥2 criteria of SIRS along with a documented underlying infectious cause were recorded as septic (32/90, 35%). A SIRS grading >2 ( p = .001) and an APPLEfast score > 25 ( p = .03) were associated with mortality. Twenty-two of SIRS dogs (24%) showed circulating NRBCs. The occurrence of circulating NRBCs was associated with the mortality in SIRS groups ( p = .0025). The median NLR was 11.69 and NLR was lower in septic dogs compared to non-septic ones ( p = .0272). APPLEfast, SIRS grading and circulating NRBCs may be considered as negative prognostic factors in canine SIRS. NLR could be a useful tool in dogs with SIRS, which was significantly lower in the septic group. Further prospective, large-scale studies investigating BLR and BNLR in canine SIRS are warranted. Highlights: The majority of SIRS dogs showed a mild, micro-normocytic normochromic anemia. Circulating NRBCs could has additional negative prognostic value in canine SIRS. The evaluation of NLR could be an interesting tool in dogs with SIRS.